A morphometric evaluation of nasal septum in patients with rhinosinusitis and association with its severity - Ismail, Zul Izhar Mohd (Pusat Pengajian Sains Perubatan, 2020)
Nasal septum formed a medial wall of nasal cavity. Embryologically, the nasal septum is thought to develop as a fold growing downward between the paired nasal cavities until it reaches the palatal shelves. Its growth is thought to be in an inferior direction from the nasofrontal prominence (Neskey and Casiano, 2009). The septum was believed to grow as a free process that projected from the craniofacial complex. Then it continues to grow and fuses with the palatal shelves to form the secondary palate. The anterior portion of the septum is continuous with the nasomedial processes and combines to form the primary palate. The cartilaginous nasal capsule surrounds the cavity and is continuous with the nasal septum. The capsule further develops to form the lateral nasal wall until its completion at 24 weeks gestation (Neskey and Casiano, 2009). Anatomically it consists of bone and cartilage (Figure 1.4). The triangular vomer, articulating above with the sphenoid body form the posterior border of the septum. Inferiorly it is slotted into the grooved ridge on the hard palate and extends beyond the incisive canal. The vomer is grooved on each side by the nasopalatine nerves. The perpendicular plate of the ethmoid articulates with the upper margin of the vomer but not throughout its length. The septal cartilage, the unossified part of the ethmoid’s perpendicular plate, forms the anterosuperior part of the septum. Inferiorly it is slotted into a bony groove at its vomerine and maxillary articulations. The nasal septum is frequently deviated from the midline and small bony spurs may project from the septal surface into the nasal cavity. The anteroinferior corner of the septum is mobile, being formed by the medial crura of the paired major alar cartilages.